Жизнь и деятельность Балтазара Коссы. Папа Иоанн XXIII - Парадисис Александр (Такт, 1991)
Экземпляры: Пф (1991) / Инвентарный номер: 23594 / Цена: / Авт.знак: П 18 / ГРНТИ: 17.82.31 / ББК: 84(4Гре)6-4